2006
DOI: 10.1093/mutage/gel029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic damage in operating room personnel exposed to anaesthetic gases

Abstract: Information on potential genetic damage in humans after exposure to waste anaesthetic gases in Indian hospitals is scarce. To evaluate the possible genotoxic effects of waste anaesthetic gases, the chromosomal aberrations analysis and comet assay were studied in peripheral blood lymphocytes in 45 operating room personnel currently employed at a hospital in South India. In addition, the micronucleus test on buccal epithelial cells was also carried out in the same subjects. The exposed group was compared with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
3
50
1
5
Order By: Relevance
“…Many studies have suggested that chronic exposure to trace levels of anesthetic gas is harmful to operating room personnel despite developed scavenging systems [2,[17][18][19][20]. To our knowledge, this is the first study to interpret the association between impaired oxidative balance and HDL-related PON1, ARE enzyme activity, and AP.…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have suggested that chronic exposure to trace levels of anesthetic gas is harmful to operating room personnel despite developed scavenging systems [2,[17][18][19][20]. To our knowledge, this is the first study to interpret the association between impaired oxidative balance and HDL-related PON1, ARE enzyme activity, and AP.…”
Section: Discussionmentioning
confidence: 79%
“…Wiesner et al found a higher MN level in anaesthesiologists and nurses exposed to high levels of halothane and isoflurane compared with a control group 1) . Chandrasekhar et al reported a statistically significant increase in DNA damage as shown by CA, MN and the comet assay in operating room personnel exposed to anaesthetic gases 16) . Although we couldn't evaluate the exposure levels to anaesthetic gases, our study points to an increase in DNA damage in anaesthesia nurses working in operating rooms with artificial ventilation and active scavenging systems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown increased DNA damage, assessed by sister chromatid exchange (SCE), chromosomal aberration (CA) and micronuclei (MN) tests in operating room personnel exposed for several years to waste anesthetic gases [10][11][12][13][14][15][16][17] . However, there is still no report about the effect of waste anesthetic gases in professionals occupationally exposed for a shorter time.…”
Section: Introductionmentioning
confidence: 99%